Testing the Predictive Power of Its Dimensions in Explaining the Intention to use Mobile Learning Systems in Universities-Empirical Evidence from Ugandan Universities - Mubuke, Faisal; Mayoka Kituyi, Geoffrey; Masaba, Kutosi Ayub (Journal of Educational Technology Systems, 2018)
Among information systems, mobile learning systems are acknowledged for the exponential growth in recent years into education sector specifically in the higher education learning institutions. Mobile learning systems are viewed as a kind of information system, which universities use to better serve their students efficiently and effectively in order to provide sustainable value for education. While past studies from numerous scholars positioned their focus on development of mobile learning frameworks to enhance the usage of mobile learning systems. Comparatively, little research has been conducted to explore the predictive, positional, and potential influence of social influence and its dimensions on student's intention to continuously use mobile learning systems in universities of developing countries like Uganda. This study used a cross sectional survey methodology to gather data from a sample size of N=375 students from both public and private universities. The results of correlation and regression analysis revealed significant positive relationship between social influence and the intention to use M-learning systems in Ugandan universities, implying that social influence is a significant determinant of student's intentions to use M-learning systems in Uganda. Additionally, social influence significantly impacts student's intention to use mobile learning systems. Social influence as presented in this study, explain 34.90% variation in enhancing student's intention to use mobile learning systems in Ugandan universities. Therefore, universities should pay meticulous attention to social influence as one of the major determinants and predictors needed to enhance student's intention to use M-learning systems.
Keywords: M-Learning; Social Influence; Intention to Use; ICT; MoICT